Laparoscopic sentinel node navigation surgery versus laparoscopic gastrectomy with lymph node dissection for early gastric cancer: short‐term outcomes of a multicentre randomized controlled trial (SENORITA). Issue 11 (3rd June 2020) - An, J. Y.; Min, J.‐S.; Hur, H.; Lee, Y. J.; Cho, G. S.; Park, Y.‐K.; Jung, M. R.; Park, J.‐H.; Hyung, W. J.; Jeong, S.‐H.; Kim, Y.‐W.; Yoon, H. M.; et al.
Abstract : Background: Sentinel node navigation surgery reduces the extent of gastric and lymph node dissection, and may improve quality of life. The benefit and harm of laparoscopic sentinel node navigation surgery (LSNNS) for early gastric cancer is unknown. The SENORITA (SEntinel Node ORIented Tailored Approach) trial investigated the pathological and surgical outcomes of LSNNS compared with laparoscopic standard gastrectomy (LSG) with lymph node dissection. Methods: The SENORITA trial was an investigator‐initiated, open‐label, parallel‐assigned, non‐inferiority, multicentre RCT conducted in Korea. The primary endpoint was 3‐year disease‐free survival. The secondary endpoints, morbidity and mortality within 30 days of surgery, are reported in the present study. Results: A total of 580 patients were randomized to LSG (292) or LSNNS (288). Surgery was undertaken in 527 patients (LSG 269, LSNNS 258). LSNNS could be performed according to the protocol in 245 of 258 patients, and a sentinel node basin was detected in 237 (96·7 per cent) Stomach‐preserving surgery was carried out in 210 of 258 patients (81·4 per cent). Postoperative complications occurred in 51 patients in the LSG group (19·0 per cent) and 40 (15·5 per cent) in the LSNNS group ( P  = 0·294). Complications with a Clavien–Dindo grade of III or higher occurred in 16 (5·9 per cent) and 13 (5·0 per cent) patients in the LSG and LSNNS groups respectively ( P  = 0·647). Conclusion: The rate and severity of complications following LSNNS for early gastric cancer are comparable to those after LSG with lymph node dissection. Registration number: NCT01804998 ( http://www.clinicaltrials.gov ). Abstract : The prospective, multicentre, randomized controlled phase III SENORITA trial evaluated the surgical and oncological outcomes of laparoscopic sentinel node navigation surgery (LSNNS) compared with laparoscopic standard gastrectomy (LSG) with lymph node dissection (LND) for early gastric cancer (EGC). LSNNS for EGC is a safe procedure in terms of postoperative morbidity and mortality compared with LSG and LND. ESD, endoscopic submucosal dissection; mITT, modified intention to treat; FAS, full analysis set; OGJ, oesophagogastric junction; LDG, laparoscopic distal gastrectomy; LTG, laparoscopic total gastrectomy; LPPG, laparoscopic pylorus‐preserving gastrectomy; LPG, laparoscopic proximal gastrectomy; ODG, open distal gastrectomy; OTG, open total gastrectomy; PP, per protocol; SBD, sentinel basin dissection; EFTR, endoscopic full‐thickness resection; LWR, laparoscopic wedge resection; LSR, laparoscopic segmental resection. Similar morbidity Abstract : Antecedentes: La cirugía de navegación del ganglio centinela ( sentinel node navigation surgery, SNNS) reduce la extensión de la resección gástrica y ganglionar, y puede mejorar la calidad de vida. Se desconoce el beneficio y el daño de la cirugía de navegación del ganglio centinela por vía laparoscópica ( laparoscopic sentinel node navigation surgery, LSNNS) para el cáncer gástrico precoz. El ensayo clínico SENORITA investigó los resultados patológicos y quirúrgicos de LSNNS en comparación con la gastrectomía laparoscópica estándar ( laparoscopic gastrectomy, LSG) con disección ganglionar ( lymph node dissection, LND). Métodos: El ensayo SENORITA fue un ensayo multicéntrico aleatorizado y controlado, iniciado por investigadores, abierto, con asignación a grupos paralelos y de no inferioridad llevado a cabo en Corea. El resultado primario fue la supervivencia libre de enfermedad a los 3 años. En el presente estudio, se describen los resultados secundarios correspondientes a morbilidad y mortalidad a los 30 días del postoperatorio. Resultados: Un total de 580 pacientes fueron aleatorizados a LG ( n = 292) o LSNNS ( n = 288). La cirugía se realizó en 527 pacientes (LG 269, LSNNS 258). LSNNS pudo ser realizada de acuerdo con el protocolo en 245 de 258 pacientes y en 237 de 245 pacientes (96, 7%) se detectó un ganglio centinela. La cirugía con preservación del estómago se realizó en 210 de 258 pacientes (81, 4%). Las complicaciones postoperatorias se presentaron en 51 pacientes del grupo LSG (19, 0%) y en 40 pacientes (15, 5%) del grupo LSNNS ( P = 0, 294). Las complicaciones grado III o mayor de Clavien‐Dindo se detectaron en 16 (5, 9%) y 13 pacientes (5, 0%) de los grupos LSG y LSNNS, respectivamente ( P = 0, 647). Conclusión: El porcentaje y la gravedad de las complicaciones tras LSNNS para cancer gástrico precoz son comparables a la LSG con LND.